2007
DOI: 10.1104/pp.106.094748
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Biosynthesis in Barley Primary Leaves Requires the Presence of the Vacuole and Controls the Activity of Vacuolar Flavonoid Transport

Abstract: Barley (Hordeum vulgare) primary leaves synthesize saponarin, a 2-fold glucosylated flavone (apigenin 6-C-glucosyl-7-Oglucoside), which is efficiently accumulated in vacuoles via a transport mechanism driven by the proton gradient. Vacuoles isolated from mesophyll protoplasts of the plant line anthocyanin-less310 (ant310), which contains a mutation in the chalcone isomerase (CHI) gene that largely inhibits flavonoid biosynthesis, exhibit strongly reduced transport activity for saponarin and its precursor isovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 76 publications
2
62
0
Order By: Relevance
“…Several known flavonoid MATE transporters, including AM1, AM3, MATE1, and TT12, are localized to the tonoplast membrane, as shown by imaging of green fluorescent protein (GFP)-tagged transporters or membrane proteomics studies (Marinova et al, 2007a;Gomez et al, 2009;Zhao and Dixon, 2009). Topological prediction suggests that MATE2 has 12 putative transmembrane domains in the same pattern as other known MATE transporters (see Supplemental Figure 12 online).…”
Section: Mate2 Is a Tonoplast Transporter Whereas Flavonoid Malonyltmentioning
confidence: 94%
See 2 more Smart Citations
“…Several known flavonoid MATE transporters, including AM1, AM3, MATE1, and TT12, are localized to the tonoplast membrane, as shown by imaging of green fluorescent protein (GFP)-tagged transporters or membrane proteomics studies (Marinova et al, 2007a;Gomez et al, 2009;Zhao and Dixon, 2009). Topological prediction suggests that MATE2 has 12 putative transmembrane domains in the same pattern as other known MATE transporters (see Supplemental Figure 12 online).…”
Section: Mate2 Is a Tonoplast Transporter Whereas Flavonoid Malonyltmentioning
confidence: 94%
“…Dysfunction of the vacuole or loss of function of vacuolar flavonoid transporters can reduce flavonoid accumulation (Marinova et al, 2007a(Marinova et al, , 2007b. The ABC transporter MRP3 and a few MATE transporters (AM1 and AM3) have been suggested to transport anthocyanins into the vacuole (Goodman et al, 2004;Gomez et al, 2009).…”
Section: Discussion Substrate Preferences For Flavonoid Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…These metabolites may otherwise display adverse activities for the producing plant cell. Intracellular storage of such biologically active metabolites in the vacuole is well established for water-soluble compounds and for compounds that become water soluble through conjugation (Marinova et al, 2007;Ferreres et al, 2011;Zhao et al, 2011;Li et al, 2012b). Similarly, for the large class of often-lipophilic terpenoids, it has been suggested that their intracellular accumulation may be limited by nonspecific interference with cellular Figure 6.…”
Section: In Planta Heterologous Expression and Functional Characterizmentioning
confidence: 99%
“…Once the biosynthesis is completed, including the additional chemical modifications (glycosylation, methylation, and acylation;Winkel-Shirley, 2008), anthocyanins are transported into the vacuole. A report has shown that vacuolar accumulation of flavonoids is a prerequisite for their biosynthesis and thus fulfils a regulatory function during synthesis (Marinova et al, 2007a). The mechanisms by which anthocyanins are transported into the vacuole have long been debated.…”
Section: Introductionmentioning
confidence: 99%